Fracture resistance of teeth restored with different resin-based restorative systems - Willian Yoshio Kikuti; Fernanda Oliveira Chaves; Vinicius Di Hipólito; Flávia Pires Rodrigues; Paulo Henrique Perlatti D'Alpino (Sociedade Brasileira de Pesquisa Odontológica, 2012)
The aim of the present study was to evaluate the fracture resistance of teeth restored with resin composite. Forty-eight maxillary premolar teeth were chosen and randomly divided to six groups: G1 (control): sound teeth; G2: MOD preparation, unrestored; G3: MOD + Adper Single Bond 2/P60; G4: MOD + Adper Easy One/P60; G5: MOD + P90 restorative system; G6: MOD + Adper Easy One/P90 Bond/P90. Specimens were subjected to compressive axial loading (0.5 mm/min). Flexural strength and the modulus of elasticity were also tested (n = 7). The only statistical equivalence with sound teeth was noted for G3 (p < 0.05). Flexural strength and the modulus of elasticity varied among the composites tested (n = 10). The reestablishment of the resistance to fracture in premolars subjected to Class II MOD preparations is restorative-system-dependent. The silorane restorative system is not able to recover the resistance to fracture.